2016
DOI: 10.1038/srep20164
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin participates in beta-amyloid transport from the brain to the liver- involvement of the low-density lipoprotein receptor-related protein 1?

Abstract: Transthyretin (TTR) binds Aβ peptide, preventing its deposition and toxicity. TTR is decreased in Alzheimer’s disease (AD) patients. Additionally, AD transgenic mice with only one copy of the TTR gene show increased brain and plasma Aβ levels when compared to AD mice with both copies of the gene, suggesting TTR involvement in brain Aβ efflux and/or peripheral clearance. Here we showed that TTR promotes Aβ internalization and efflux in a human cerebral microvascular endothelial cell line, hCMEC/D3. TTR also sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 40 publications
(57 reference statements)
1
91
0
Order By: Relevance
“…TTR is described as a transporter of T 4 and retinol; however, more recently it has been shown to be a binding partner for Aβ and suggested to be intimately involved in its clearance from the brain (17). As for resveratrol, apart from its potent antioxidant properties, several studies have demonstrated that this polyphenol also plays a neuroprotective role, although the mechanism by which this is performed is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TTR is described as a transporter of T 4 and retinol; however, more recently it has been shown to be a binding partner for Aβ and suggested to be intimately involved in its clearance from the brain (17). As for resveratrol, apart from its potent antioxidant properties, several studies have demonstrated that this polyphenol also plays a neuroprotective role, although the mechanism by which this is performed is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…When TTR was genetically decreased, mice presented higher levels of Aβ (both Aβ 40 and Aβ 42 ) in the brain and plasma, accompanied by higher Aβ deposition (15,16) compared with control mice. This showed that TTR is an important molecule in the clearance of Aβ, with recent findings suggesting that TTR promotes Aβ efflux from the brain to the blood, possibly via LRP1 (17), although the exact mechanism is still unknown.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…TTR cleaves Aβ at multiple positions to degrade aggregated forms of Aβ. In vivo studies suggested that TTR can transport Aβ from the brain to blood but not into the brain [16]. TTR crosses the monolayer of cells only in the brain-to-blood direction.…”
Section: Introductionmentioning
confidence: 99%
“…TTR crosses the monolayer of cells only in the brain-to-blood direction. TTR-mediated Aβ clearance is through LRP1, as lower receptor expression was found in brains and livers of TTR knockdown mice and in cells incubated without TTR [16] [17]. The activated TTR may contribute not only to the upholding of Aβ levels within a normal range but also to the degradation of deposited Aβ in the case of imbalance and diseases condition [18].…”
Section: Introductionmentioning
confidence: 99%